2005
DOI: 10.1111/j.1537-2995.2005.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of posterior subcapsular cataracts in granulocyte donors

Abstract: This study does not support the hypothesis that corticosteroid stimulation of PMN donors is associated with an increased risk of developing a PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 17 publications
0
30
0
2
Order By: Relevance
“…The higher risk of the development of posterior subcapsular cataract (PSC) in granulocyte donors was initially reported by Ghodsi and Strauss [33]. Two other studies [34,35] published more recently could not confirm a significant higher incidence of PSC in granulocyte donors compared with platelet donors. In spite of that, both studies revealed a clear association of PSC frequency with the number of granulocyte donations and the cumulative dose of steroids.…”
Section: Discussionmentioning
confidence: 69%
“…The higher risk of the development of posterior subcapsular cataract (PSC) in granulocyte donors was initially reported by Ghodsi and Strauss [33]. Two other studies [34,35] published more recently could not confirm a significant higher incidence of PSC in granulocyte donors compared with platelet donors. In spite of that, both studies revealed a clear association of PSC frequency with the number of granulocyte donations and the cumulative dose of steroids.…”
Section: Discussionmentioning
confidence: 69%
“…There may also be a relationship between iron and platelet activity 33 . Recent studies involving large blood donor databases did not demonstrate an increased of cancer incidence 17 , degenerative brain diseases 34 , ocular disease 35 and diabetes mellitus type 2 36 , whereas an increased risk of upper extremity deep vein thrombosis was reported. Low serum iron levels have been linked with elevated plasma levels of coagulation factor VIII and venous thromboembolic risk 37 .…”
Section: Discussionmentioning
confidence: 97%
“…2.8.1.2 Corticosteroids It remains controversial whether the administration of corticosteroids along with G-CSF stimulation to granulocyte donors increases the risk of posterior subcapsular cataract [33,34]. However, the administration of corticosteroids to granulocyte donors, especially in frequent donations, should be used with caution.…”
Section: Complications Of Gtx Therapymentioning
confidence: 95%